MINERALOGICAL AND CHEMICAL COMPOSITION OF CFB FLY ASH DERIVED FROM CO-COMBUSTION OF XYLITE AND BIOMASS - Koukouzas, N.; Hämäläinen, J.; Papanikolaou, D.; Tourunen, A.; Jäntti, T. (Bulletin of the Geological Society of Greece, 2007)
The chemical and mineralogical composition of fly ash samples collected from different parts of two Circulating Fluidised Bed (CFB) facilities has been investigated. The fuels used, were Greek xylite/suhbituminous coal (from the Fiorina basin), Polish coal (from the Catowice region - Poland) and wood chips (Swedish conifer). The characterisation of the fly ash samples included chemical analyses, particle size distribution and X-ray diffraction. According to the chemical analyses the produced fly ashes are rich in CaO. Moreover, S1O2 is the dominant oxide in fly ash with Al203 and Fe2Oi found in considerable quantities. Finally, results obtained by XRD showed that the major mineral phase of fly ash is quartz, while other mineral phases that are occurred are maghemite, hematite, periclase, rutile, gehlenite and anhydrite, while the aforementioned mineral phases were identified by scanning electron microscope (SEM).